(untitled) (Research, Society and Development, 2021)
The objective of this study was to analyze the scientific productions on nursing care for patients with PPL, in order to have an understanding of the care provided. It is an integrative literature review, of a descriptive nature and qualitative approach, through the search in the databases of Latin American and Caribbean Literature in Health Sciences and in the Medical Literature Analysis and Retrieval Sistem Online via Virtual Health Library, using Health Sciences Descriptors: Nurse, Assistance and Pressure Injury in association with the Boolean operator AND, obtaining a total of 10 articles to compose the study. It can be noted the importance of the knowledge and assistance of the nursing professional in the face of the patient with LPP. The importance of qualified nurse assistance based not only on empirical knowledge, but mainly in the scientific context, keeping up-to-date for a better understanding on how to prevent and treat a PPL, so that there are no more than normal losses for the family. and for the patient who needs this care.